Neighborhood deprivation and adverse perinatal outcomes in Sweden: A population‐based register study. (8th March 2019) - Hesselman, Susanne; Wikström, Anna‐Karin; Skalkidou, Alkistis; Sundström‐Poromaa, Inger; Wikman, Anna
Abstract: Introduction: Neighborhood deprivation has been associated with adverse perinatal outcomes but it is unclear to what extent maternal and social risk factors explain the association and how a stressful environment per se contributes. Material and methods: A population‐based register study including 218 030 deliveries in Sweden between January 2013 and July 2017 was conducted. Exposure was living in a deprived or severely deprived area defined by the National Operations Department of the Swedish Police Authority. Adverse perinatal outcomes included preterm births, small‐for‐gestational‐age births and stillbirths. A propensity score‐based method was used to control for individual baseline characteristics. Associations were investigated with logistic regression analyses and risk estimates are presented as crude (OR) and adjusted odds ratio (aOR) with 95% confidence interval (CI). Results: Living in a deprived neighborhood in Sweden was associated with extremely preterm births (deprived area OR 1.50, 95% CI 1.07‐2.11, severely deprived OR 1.90, 95% CI 1.40‐2.58), small‐for‐gestational‐age birth (deprived OR 1.45, 95% CI 1.31‐1.60, severely deprived OR 1.85, 95% CI 1.69‐2.03) and stillbirth (deprived OR 1.62, 95% CI 1.17‐2.26, severely deprived OR 1.56, 95% CI 1.11‐2.19). After accounting for individual maternal and social risk factors, the risk of small for gestational age in severely deprived areas remained (aOR 1.45, 95% CI, 1.19‐1.75). Conclusions: The contextual effect of living in a deprived neighborhood on the risk of extremely preterm births, small‐for‐gestational‐age births and stillbirths was to a high extent explained by individual factors of women residing in exposed areas, yet remained for small‐for‐gestational‐age births in severely deprived areas after adjustment for maternal and social risk factors.